Dose-response effect of exercise frequency on bone mineral density in post-menopausal, osteopenic women - Kemmler, Wolfgang; von Stengel, Simon (Scandinavian journal of medicine & science in sports, 2014)
The purpose of this study was to determine the long-term dose-response relationship of exercise frequency on areal bone mineral density (aBMD) in early post-menopausal women with osteopenia. Based on the 12-year results of the consequently supervised exercise group (EG) of the Erlangen Fitness and Osteoporosis Prevention Study, we retrospectively structured two exercise groups according to the overall exercise frequency. Changes in aBMD at lumbar spine and proximal femur as assessed by dual-energy x-ray absorptiometry technique were compared between a low-frequency exercise group (LEF-EG, n = 16) with 1.5-<2 sessions/week and a high-frequency exercise group (HEF-EG, n = 25) with >= 2-3.5 sessions/week. Changes in aBMD at the lumbar spine and proximal femur were significantly more favorable in the HEF-EG compared with the LEF-EG; lumbar spine: (mean value ± standard deviation) 1.1 ± 4.7% vs -4.1 ± 3.0%; P = 0.001, ES: d' = 1.26; total hip: -4.4 ± 3.9% vs -6.7 ± 3.5%, P = 0.045, ES: d' = 0.70). BMD results of the LEF-EG did not significantly differ from the data of the non-training control group (lumbar spine: -4.4 ± 5.2%, total hip: -6.9 ± 5.0%). Although this result might not be generalizable across all exercise types and cohorts, it indicates that to impact bone, an overall exercise frequency of at least 2 sessions/week may be crucial, even if exercise is applied with high intensity/impact.
EVALuna2:10078